Economic integration for development in Eastern and Southern Africa: assessment and prospects. - MWASE, Ngila (1995)
Discusses regional economic integration schemes in Eastern and Southern Africa, their theoretical basis, current status and the actual and potential efforts to transform them into meaningful instruments for cross-border economic change. Presents the discussion in the context of changing regional dynamics in Southern Africa.